Another stage of development: Biological degeneracy and the study of bodily ageing. (April 2017) - Mason, Paul H.; Maleszka, Ryszard; Dominguez D., Juan F.
Highlights: Degeneracy refers to the interchangeability of variable structures to achieve plastic functional outcomes. Multiple networks of cortical neurons subserve similar cognitive outputs, whether that output is functional or dysfunctional. Movement science is a primary research area where degeneracy can be productively studied in human ageing. Rodents, insects and nematodes are model organisms for studying degeneracy in ageing at the cellular and molecular levels. Establishing how different structures can perform similar tasks is fundamental for developing robust frameworks of ageing. Abstract: Ageing is a poorly understood process of human development mired by a scientific approach that struggles to piece together distributed variable factors involved in ongoing transformations of living systems. Reconfiguring existing research paradigms, we review the concept of 'degeneracy', which has divergent popular and technical definitions. The technical meaning of degeneracy refers to the structural diversity underlying functional plasticity. Degeneracy is a distributed system property that can be observed within individual brains or across different brains. For example, dementias with similar behavioural anomalies can result from a diverse range of cellular "faults", which is an example of degeneracy because the symptoms are similar in spite of different underlying mechanisms. Degeneracy is a valuable epistemological tool that can transformatively enhance scientific models of bodily ageing. We propose that movement science is one of the first areas that can productively integrate degeneracy into models of bodily ageing. We also propose model organisms such as eusocial honey bees in which degeneracy can be studied at the molecular and cellular level. Developing a vocabulary for thinking about how distributed variable factors are interlinked is important if we are to understand bodily ageing not as a single entity, but as the heterogeneous construction of changing biological, social, and environmental processes.